Development of the structure and content of SCRUM-technologies of control of fast-flowing medical projects with critical risks - Stanovska, Iraida; Heblov, Ismaail; Guriev, Ivan; Koshuljan, Sergiy (Technology audit and production reserves, 2017)
The object of research is a project (for example, a surgical operation), which, while preserving all the basic properties of the project (uniqueness, limited time, economic and material resources, carried out by the Project Team for a given purpose in cooperation with the turbulent environment), has a number of specific features. These features include fast flow and high responsibility for the result, which make it possible to distinguish project management in a special class of project activity. A problematic place in the research object is the forced need for redistribution of the roles of the project participants. The project team should be small, mobile and multifunctional. The owner of the project product, who is also a patient, is simultaneously an interested person in the successful completion of the project and the most «detached» from making any decisions in choosing the structure and content of the project technologies. A system for the proactive management of the structure and content of operations based on SCRUM-technologies is proposed. The peculiarity of the system is that it allows to estimate the probability of occurrence of internal and external significant risk events and to change the originally planned sequence of Sprints in SCRUM-technology under the influence of this assessment. When managing the draft selection of treatment strategy and tactics within the SCRUM-technology of special treatment in patients with disseminated common abdominal tumors, the high positive statistical clinical effect of such tests has been officially confirmed. This is due to the fact that the proposed method of project management allows to anticipate and prevent the risks of the operation, both during its conduct and for the subsequent control (1 year) period of patients’ life. Thanks to this, the resectability of the primary tumor increased to 65 % in comparison with the control group, the quality of life improved by 43% and the number of patients whose life expectancy exceeded 1 year after diagnosis and treatment started increased by 23 %.